(3GdeQbGI GdhajI Edi WHbGJ GdMfajIs - (3eMeO Hf jYbhH Hf eMeO Hf EHQGgje Hf YeQ, CHh WGgQ, eLO GdOjf GdTjQGRj GdajQhRBHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3hHYO , agPG eNJUQ CPcQ ajg CSeGA ef Jabg HePgH GdEeGe CHj MfjaI QMeg Gddg JYGdi s
(3BNQgG (B:s
(3eHJhQ GdBNQ , hBNQ GdehLhO efg (B: (3eMeO Hf jMji Hf egOi , CHh YHO Gddg GdLQLGfi hYfg CHh SYO GdSeGf , hCHh fUQ GdTjQGRi , eGJ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B118s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B236 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B387 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs